Prequel: An American Fight Against Facism - Maddow, Rachel (PenguinRandomHouse, 2023)
Rachel Maddow traces, with the help of archival and published material, the fight to preserve American democracy back to World War II, when a handful of committed public servants and brave private citizens thwarted far-right plotters trying to steer our nation toward an alliance with the Nazis.
United States of America
Keywords: 2023-10 October; Facism